Effectiveness of Implementing Information Technology Governance in the Education Sector Based on the Cobit 5 Measurement Model: A Systematic Literature Review - Audrey Septya Rosanti; Natasya Eka Damayanti; Anita Wulansari (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
To effectively implement information technology governance in educational institutions and achieve desired outcomes, the COBIT 5 framework presents itself as a valuable tool. COBIT 5 offers comprehensive services for managing resources and overseeing information technology governance processes. In this study, the author employs the Systematic Literature Review method to gather a diverse array of data pertaining to the COBIT 5 framework's application within educational contexts. The research findings delve into several key areas, including the utilization of COBIT 5 to enhance and bolster human resources within the education sector, its efficacy in educational settings, and its impact on educational quality standards. This study contributes novel insights by examining the multifaceted role of the COBIT 5 framework specifically within the realm of educational institutions. By exploring its application in enhancing human resources, effectiveness, and educational quality, this research offers valuable perspectives for educators and IT governance professionals seeking to leverage COBIT 5 for optimized educational outcomes.